(untitled) (KEMANUSIAAN The Asian Journal of Humanities, 2019)
This paper analyses the structure of authorities and syncretic practices among the people in South East Asia before the spread of Islam in the region. The influence of South Asian tradition and culture in South East Asia was evident especially in the social and political spheres. Practices of South East Asian empires originated from the South Asian continent. In order to understand those influences, this study analyses available materials related to the development of socio-political and cultural-religious environment in South East Asia prior to the advancement of Islam in the region. This study concludes that early kingdoms in South East Asia adopted the doctrines of devaraja and bodhisattva as the model of governance. This doctrine provides the rulers with everlasting loyalty from their subjects. At the same time, religious life among the people in South East Asia highlights a unique practice. The syncretic practices of the people in South East Asia at that time prove that they did not follow blindly religious practices presented to them from the South Asian traditions. They adopt and adapt those practices to suit their own needs at that time.